2016
DOI: 10.4136/ambi-agua.1929
|View full text |Cite
|
Sign up to set email alerts
|

Vigilância e monitoramento de fluoretos em águas de abastecimento público: uma revisão sistemática

Abstract: RESUMOO fluoreto presente na água pode ser um fator de proteção ou de risco à dentição humana dependendo da sua concentração. O objetivo foi sumarizar as principais características metodológicas e os principais achados descritos em estudos sobre monitoramento da concentração de fluoreto em água de abastecimento público, que foram publicados em revistas científicas especializadas entre 2008 e 2012, examinando suas implicações para a vigilância em saúde pública. Uma revisão sistemática foi realizada buscando art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 11 publications
0
10
0
12
Order By: Relevance
“…This normative device is outdated and needs to be revised (Frazão et al, 2011). In addition, because it presents a dichotomous classification, experts have noted that it is an undesirable interpretative reduction (Venturini et al, 2016), and have emphasized that it does not consider the balance between benefits and risks to health (Frazão et al, 2011). Although most of the studies (75%) used the dichotomous (adequate/inadequate) classification criterion, it is acknowledged that these narrow down the options for interpretation and attribution of meaning to the characteristics of the samples (Cecol, 2011;Bergamo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This normative device is outdated and needs to be revised (Frazão et al, 2011). In addition, because it presents a dichotomous classification, experts have noted that it is an undesirable interpretative reduction (Venturini et al, 2016), and have emphasized that it does not consider the balance between benefits and risks to health (Frazão et al, 2011). Although most of the studies (75%) used the dichotomous (adequate/inadequate) classification criterion, it is acknowledged that these narrow down the options for interpretation and attribution of meaning to the characteristics of the samples (Cecol, 2011;Bergamo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Systematic assessment revealed a potential discontinuity characterized by concentration values not complying with the legislation and being below the level prescribed to prevent tooth decay, reinforcing the warnings of several researchers regarding the need to expand water fluoridation monitoring systems. While not exposed to the risk of dental fluorosis, the population would be deprived of the maximum benefit provided by an adequate level of fluoride in water (Venturini et al, 2016). Except for a study that found increasing rates of fluoridation standard compliance according to the scale of the supply systems and the values of the HDI (Daré et al, 2009), information on the relationship between the quality level of fluoridation and municipal-level indicators related to sanitation, health, economic and income inequality variables is scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the scientific literature involving Brazilian studies revealed that most non-conformity situations concerning fluoride concentration did not represent immediate health risk for the population, as they referred to hypo-fluoridation situations -that is, fluoride level below the recommended for preventing dental caries 18 . Despite such evaluation, monthly data obtained when following the Program in each municipality have inestimable value, and should not be discarded or abandoned in database and electronic files of surveillance agencies.…”
Section: The Vigifluor Systemmentioning
confidence: 99%
“…Quando esse monitoramento é feito a partir da observação de amostras da água por organismo distinto daquele que é responsável pelo sistema de fluoretação, ele é chamado de heterocontrole (NARVAI, 2000a). Quando o monitoramento é parte da ação permanente do Estado, é chamado de vigilância (VENTURINI et al, 2016).…”
Section: Introductionunclassified